Human papillomavirus infection and its vaccines: Knowledge and attitudes of primary health clinic nurses in Kelantan, Malaysia - Norwati, Daud; K, Jeyachelvi; Juwita, Shaaban (2016)
Background: Cervical cancer though preventable is still the leading cause of cancer death among women secondary to breast cancer. Persistent infection with HPV has been causally linked to the disease. A school based HPV vaccination program was introduced in late 2010 in Malaysia and nurse support is essential for its success.